THE INHERITANCE OF THE FIBER YIELD TRAIT IN F1 PLANTS OBTAINED AS A RESULT OF CROSSBREEDING IN SOME INTRASPECIFIC VARIETIES OF THE G.HIRSUTUM L. (Multidisciplinary Journal of Science and Technology, 2024)
This article analyzes the inheritance and variability of the fiber yield trait in F1 plants obtained by hybridization with certain subspecies and cultivated varieties of the species G.hirsutum L. The fiber yield in F1 plants obtained as a result of crossbreeding certain subspecies and cultivated varieties belonging to the species G.hirsutum L. is the utmost importance from a breeding perspective.